Changes in the Oral-Health-Related Quality of Life of Thai patients with oral lichen planus after topical corticosteroid treatment: a 1-month longitudinal study - Witchapat Kengtong; Pornpan Piboonratanakit; Sudaduang Krisdapong (BMC, 2023)
Abstract Background Oral lichen planus (OLP) is a chronic inflammatory disease of the oral cavity that affects many patients' daily living activities. Topical corticosteroids are the first-line drug for treating OLP. The Oral Impact on Daily Performances index (OIDP) is an Oral-Health-Related Quality of Life (OHRQoL) measure developed to assess the ultimate impacts. The aims of this study were to evaluate the clinical, pain and OHRQoL responses after treating OLP patients with topical corticosteroids for 1 month, and secondly to assess the relationships of changes in the clinical sign score, pain score, and OHRQoL. Methods Seventy-two OLP patients were treated by topical corticosteroids based on their dentists' clinical judgments. Clinical and patient-based outcomes were assessed at baseline and follow-up visit. The clinical outcomes were evaluated by the highest and total Thongprasom sign score. Patient-based outcomes were evaluated by numeric rating scale (NRS) and OIDP. The self-rated overall changes in quality of life during the 1-month treatment period using the Patient Global Impression of Change (PGIC) were also recorded at the follow-up visit. Results This study comprised 59 women and 13 men. All clinical and patient-based outcomes were significantly reduced after 1-month treatment with topical corticosteroids (P < 0.01). The most commonly affected activities were Emotional stability, followed by Eating and Cleaning the oral cavity. Forty-six percent reported the same or up to moderately improved, while 54% had a greatly improved quality of life as assessed by PGIC. There were no significant differences in the improvement of clinical and patient-based outcomes between these groups. There were significant relationships between the differences in the highest Thongprasom sign score and the differences in total Thongprasom sign score (r = 0.293; P < 0.05), and the differences in total OIDP percentage score and the difference in pain score (r = 0.427; P < 0.001). The differences in the total Thongprasom sign score also significantly related to the difference in the total OIDP percentage score (r = 0.335; P < 0.01). Conclusions Topical corticosteroids were significantly effective after 1-month treatment of OLP based on the clinical and patient-based outcomes. The OHRQoL improvement was significantly related to the reductions in pain and clinical severity. Trial registration The trial was registered at the Thai Clinical Trials Registry (TCTR identifier: TCTR 20221110001).